The Role of Adverse Childhood Experiences on Psychological Well-being among College Students: The Mediating Role of Emotional Intelligence - Morinawa, Salsabilla; Soleh, Achmad Khudori (Journal of Educational, Health and Community Psychology, 2025)
This study aims to examine the effect of Adverse Childhood Experiences (ACEs) on Psychological Well-Being (PWB) among college students, with Emotional Intelligence (EI) as a mediating variable. Although ACEs are widely known to affect mental health, research exploring the psychological mechanisms underlying this relationship in Indonesian college student populations remains limited. Using a quantitative explanatory design and purposive sampling, 440 students aged 18–25 years completed standardized measures of ACEs, EI, and PWB. Data were analyzed using PROCESS Macro Model 4 with 5,000 bootstrap resamples. Results showed that ACEs had a significant negative effect on PWB (B = -0.651, t = -5.464, p < .001), whereas EI had a significant positive effect on PWB (B = 0.722, t = 12.475, p < .001). EI also partially mediated the effect between ACEs and PWB, emphasizing the importance of enhancing emotional intelligence in educational settings. These findings highlight the importance of strengthening emotional intelligence to mitigate the adverse impact of early negative experiences on psychological well-being.